2012
DOI: 10.1093/rpd/ncs258
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the collective dose in the Portuguese population due to medical procedures in 2010

Abstract: In a wide range of medical fields, technological advancements have led to an increase in the average collective dose in national populations worldwide. Periodic estimations of the average collective population dose due to medical exposure is, therefore of utmost importance, and is now mandatory in countries within the European Union (article 12 of EURATOM directive 97/43). Presented in this work is a report on the estimation of the collective dose in the Portuguese population due to nuclear medicine diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…Though the major part of medical exposure comes from diagnostic X-rays, it has been shown that contribution of nuclear medicine (NM) diagnostic procedures in most developed countries is between 4% and 14% [4–6]. …”
Section: Introductionmentioning
confidence: 99%
“…Though the major part of medical exposure comes from diagnostic X-rays, it has been shown that contribution of nuclear medicine (NM) diagnostic procedures in most developed countries is between 4% and 14% [4–6]. …”
Section: Introductionmentioning
confidence: 99%
“…Optimal collimation reduces (scatter) radiation and improves image quality, especially contrast and resolution [20]. Although radiation doses for individual chest radiographs are considered low [15,21], both the collective dose applied due to the volume of examinations performed [22][23][24] and the individual patient dose from repeated chest X-rays can be notable.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to known risk factors such as radiation from diagnostic tests (Schonfeld et al, 2011), including the use of iodinated contrast agents (Baker and Bhatti, 2006) and medical imaging [dental radiography (Memon et al, 2010) and computed tomography scans (Baker and Bhatti, 2006)], radiotherapy for the treatment of the head and neck malignancies (Ron et al, 1995) and exposure to environmental ionizing radiation (Richardson, 2009), has been linked to thyroid cancer, and exposure to some of these factors has increased in the last decades (Mettler et al, 2008; United Nations Scientific Committee on the Effects of Atomic Radiation, 2010). In Portugal, specifically, estimates of radiodiagnosis in 2010 were twice those observed in 1992 (Serro et al, 1992;Teles et al, 2013). As thyroid cancer is much more common in women than men, a role of female hormones in thyroid cancer has been hypothesized; however, the evidence supporting a relation between reproductive factors such as age of menarche, menopause or number of pregnancies and this type of cancer (Rahbari et al, 2010) is still The mean number of cases per year is shown: for incidence, the number of cases from 3 years was used to increase the precision of estimates from Regional Cancer Registries with small numbers of cases (2007)(2008)(2009) was selected because it is the most recent period with data available from all Regional Cancer Registries); for mortality, the number of deaths from 8 years was used for each of the Portuguese regions (2004-2012 was selected to increase the precision of estimates for regions with very small numbers of cases).…”
Section: Discussionmentioning
confidence: 93%